Reinforced concrete deep beams with openings strengthened using FRP â A review - Chin, S.C. (Trans Tech Publications Ltd, 2014)
In the modern building construction, different size of openings are provided in the web of reinforced concrete (RC) deep beams to accommodate utility pipes and ducts of essential services such as electricity cable, telephone network and air-conditioning network. However, accommodation of such openings caused reduction in beam strength, stiffness and caused excessive cracking and deflection. Many investigations were conducted to study the behaviour of openings in beams and relevant strengthening options to reinstate the lost capacity. One of the strengthening options considered lamination of fiber reinforced polymer (FRP) sheets due to its superior properties such as high tensile strength and stiffness, high resistance to corrosion, excellent fatigue performance and good resistance to chemical attack. FRP lamination has been widely accepted by the research community and practicing engineers in the construction industry as the material for strengthening and rehabilitation of common problems. However, quite limited literatures contained the use of FRP to strengthen RC deep beams with openings. This paper discussed the review of eleven different articles contained study of RC deep beams with openings together with effects of strengthening using FRP sheets. The outcome of this review paper outlined the way forward and future research focus in this area. Â© 2014 Trans Tech Publications, Switzerland.